Pengaruh Penambahan Molases dan Isolat Bakteri Asam Laktat dari Cairan Rumen Sapi PO Terhadap Kualitas Silase Rumput Gajah (Pennisetum purpureum) - Ismail Jasin (Jurnal Agripet, 2014)
(The effect of molasses and lactic acid bacteria isolated from rumen fluid of PO cattle on napier grass silage quality)ABSTRACT. The objective of this study was to evaluate the effect of molasses as carbohydrate source and inoculums of lactic acid bacteria (LAB) incubated from PO cattles rumen fluid on the quality of Napier grass (pennisetum purpureum) silages. The research was conducted at Gemawang village Jambu District Semarang Regency. Feed analysis was carried out in Laboratory Biochemical Nutrition, Animal Feed Science, Animal Science Faculty, Gadjah Mada University. This study was assigned into Completely Randomized Design with 4 treatments and 3 replicated. The treatments were addition of molasses and LAB level into the Napier grass; 0, 1, 3 and 5% (w/w) and incubated for 30 days Data were analyzed using analysis of variance (ANOVA) and the significant effect was tested by Duncan ,s Multiple Range Test. The results showed that the addition of 1 5% molases significantly affected (P0,05) lactic acid content, pH, and NH3 concentration. Increasing level of molases significantly (P0,05) increased lactic acid content, decreased pH and NH3 concentration of Napier grass silage. However, among the treatment groups of 1, 3 and 5 % of molases was not significant (P0,05) different on the lactic acid content, pH and NH3 concentration. Dry matter and organic matter content of Napier grass silage were not significantly (P0,05) affected by treatments .